Code-Mixing in Online Discussion Forum among Progressive Farmer: Revealing Sundanese Culture Wisdom in Agriculture Community - Harjanti, Miko; Lubis, Djuara; Suhanda, Nani; Sumardjo, Sumardjo (Bina Nusantara University, 2018)
This research aimed to explore the cultural wisdom which encouraged the spirit to empower the community and to reveal code-mixing utilization in the conversation. This research was conducted in progressive farming communities in West Java and Banten provinces. They communicated through an ODF (Online Discussion Forum) bridged by WhatsApp Group (WAG) social networking app. Content Analysis method could reveal the wisdom of the Sundanese culture that underlined the spirit of the progressive farmers. The observation period was from August 25 - November 26, 2016. During the observation period, there were 10.313 statements emerged in the discussion. Nvivo 8 software was used to analyze discussion themes. 20 statements were displayed in the results section as they could reflect the research questions. In code-mixing Indonesian and Sundanese, the progressive farmers also expressed their efforts to nurture young farmers by conducting training. The result shows that code-mixing of Indonesian and local language as mother tongue in the discussions accelerates mutual understanding because of cultural similarity between actors. It also implies that communication technology could be utilized for maintaining indigenous cultural wisdom.